The British industrial revolution : an economic perspective - Mokyr, Joel, 1946- (Boulder ; Oxford : Westview Press, a member of the Perseus Books Group, 1999)
The Industrial Revolution remains a defining moment in the economic history of the modern world. But what kind and how much of a revolution was it? And what kind of moment could it have been? These are just some of the larger questions among the many that economic historians continue to debate. Addressing the various interpretations and assumptions that have been attached to the concept of the Industrial Revolution, Joel Mokyr and his four distinguished contributors present and defend their views on essential aspects of the Industrial Revolution. In this revised edition, all chapters including Mokyr's extensive introductory survey and evaluation of research in this field?are updated to consider arguments and findings advanced since the volume's initial 1993 publication. Like its predecessor, the revised edition of The British Industrial Revolution is an essential book for economic historians and, indeed, for any historian of Great Britain in the eighteenth and nineteenth centuries.
Kniha nabízí moderní ekonomický pohled na Britskou průmyslovou revoluci, období zásadních změn v technologiích, výrobě i společenské struktuře. Autoři zkoumají příčiny a dopady industrializace pomocí analytických metod ekonomické historie. Věnují se zejména růstu produktivity, roli inovací, proměnám pracovního trhu, vývoji životní úrovně a regionálním rozdílům. Publikace propojuje historická fakta s ekonomickými modely a poskytuje ucelený, kritický výklad toho, proč právě Británie stála v čele industrializačního procesu.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: 18.-19. století; 1760-1860; průmyslová revoluce; hospodářské dějiny; hospodářské poměry; Velká Británie; eseje; sborníky; 18th-19th centuries; industrial revolution; economic history; economic conditions; Great Britain; essays